Investigating the Perspective and Satisfaction Level of Higher Education Students in Shiraz University concerning Fulltext Databases Ebsco, ProQuest, ScienceDirect, and Elsevier - Zahir Hayati; Tahereh Jowkar (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2010)
The present research investigates the perspective of higher education students in Shiraz University, as one of the greatest educational and research centers of Iran, regarding fulltext databases such as Ebsco, Elsevier, ScienceDirect, and ProQuest. Results of the current study reveal that, students’ perspective towards accessing information through the two databases ScienceDirect and Elsevier is positive, while they have negative view regarding the two databases Ebsco and ProQuest. Furthermore, the achieved results indicate that the possibility of information storage on computers, access to most updated articles and journals, and the possibility of end-user searching have been the most significant satisfaction factors regarding the databases. Additionally, the problems of no possibility to access the databases at work place or at place of students’ residence, and no possibility of connection to these databases due to traffic of connection lines and high number of visitors, are among the most important problems the students encounter when using the databases.